Theoretical study of infrared spectra of interstellar PAH molecules with N, NH, and NH2 incorporation. (27th December 2021) - Vats, Akant; Pathak, Amit; Onaka, Takashi; Buragohain, Mridusmita; Sakon, Itsuki; Endo, Izumi
Abstract: This work presents theoretical calculations of infrared spectra of nitrogen (N)-containing polycyclic aromatic hydrocarbon (PAH) molecules with the incorporation of N, NH, and NH2 using density functional theory (DFT). The properties of their vibrational modes in 2–15 μm are investigated in relation to the Unidentified Infrared (UIR) bands. It is found that neutral PAHs, when incorporated with NH2 and N (at inner positions), produce intense infrared bands at 6.2, 7.7, and 8.6 μm that have been normally attributed to ionized PAHs so far. The present results suggest that strong bands at 6.2 and 11.2 μm can arise from the same charge state of some N-containing PAHs, arguing that there might be some N-abundant astronomical regions where the 6.2 to 11.2 μm band ratio is not a direct indicator of the PAHs' ionization. PAHs with NH2 and N inside the carbon structure show the UIR band features characteristic to star-forming regions as well as reflection nebulae (Class A), whereas PAHs with N at the periphery have similar spectra to the UIR bands seen in planetary nebulae and post-AGB stars (Class B). The presence of N atoms at the periphery of a PAH may attract H or H + to form N–H and N–H2 bonds, exhibiting features near 2.9–3.0 μm, which are not yet observationally detected. The absence of such features in the observations constrains the contribution of NH and NH2 substituted PAHs that could be better tested with concentrated observations in this range. However, PAHs with N without H either at the periphery or inside the carbon structure do not have the abundance constraint due to the absence of 2.9–3.0 μm features and are relevant in terms of positions of the UIR bands. Extensive theoretical and experimental studies are required to obtain deeper insight.